2021
DOI: 10.1371/journal.pone.0253261
|View full text |Cite
|
Sign up to set email alerts
|

Substance use is associated with worse mental health and altered resting state functional connectivity in female university athletes at baseline: A pilot study

Abstract: University athletes are at high risk for both substance use and mental health problems. This study examined associations between substance use, mental health symptoms, and the resting state functional connectivity (rsFC) of key neural regions involved in self-monitoring and emotional regulation in a sample of female varsity athletes. 31 female university athletes completed measures of substance use, mental health symptoms, and underwent functional MRI scans during the pre-season. Athletes who were substance us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has also been suggested that the OFC was involved in the processing of rewards and punishments ( 48 ), explaining the observed decision-making and goal-driven behavior abnormalities caused by BQD ( 20 ). By contrast, a recent fMRI study found that athletes who consumed alcohol or cannabis seemed to have hypoconnectivity in their left OFC relative to nonusers ( 49 ), suggesting that different types of psychoactive substances may produce inconsistent neural mechanisms ( 50 ).…”
Section: Discussionmentioning
confidence: 90%
“…It has also been suggested that the OFC was involved in the processing of rewards and punishments ( 48 ), explaining the observed decision-making and goal-driven behavior abnormalities caused by BQD ( 20 ). By contrast, a recent fMRI study found that athletes who consumed alcohol or cannabis seemed to have hypoconnectivity in their left OFC relative to nonusers ( 49 ), suggesting that different types of psychoactive substances may produce inconsistent neural mechanisms ( 50 ).…”
Section: Discussionmentioning
confidence: 90%
“…In a pilot study of female college varsity athletes, cannabis use was associated positively with depressive symptoms, and, although this study only included 31 athletes, the effect size was significant. 81 In addition, a protein associated with depression when brain-derived neurotrophic factor was found to be lower in physically active young adults who identified as chronic cannabis users compared with age-matched peers who did not use cannabis. 43 Although the mechanism is not completely understood, cannabis use has been linked to earlier onset of schizophrenia in those with preexisting risk factors and may increase the risk of development of psychotic symptoms in any user.…”
Section: Mental Healthmentioning
confidence: 99%
“…Participants are asked to indicate the extent to which they are bothered by the questionnaire items over the last 2 weeks. Questions are scored on a 4-point ordinal scale and total score is interpreted as follows; none (1-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Measures Mental Health Statusmentioning
confidence: 99%
“…15,16 A recent pilot study by our group also identified altered brain activity in self-monitoring and emotion regulation regions associated with substance use and depression symptoms in female athletes with mTBI history. 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation